Factors in the Selection of Accountancy, Business, and Management as Preferred Track of Senior High School: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Accountancy, Business, and Management strand is part of the K-12 Academic Track. Itfocuses on financial management, business management, corporate operations, andeverything that needs to be recorded. However, this study focuses on evaluating the factorsthat influenced the Grade 11 and Grade 12 ABM students in terms of choosing Accountancy,Business, and Management as their preferred track and how they perceived their track as acontribution to their future course. This study is conducted at Bestlink College of thePhilippines, Bulacan Inc.The study revealed that in terms of factors that influence students in choosing a strand,personal interest got the highest composite mean of 3.43, interpreted as strongly Agreeable.Moreover, for the research question of how respondents perceive their track as a contributionto their future course, it got a 3.53 Mean, and the interpretation of that is Strongly Agree. Thefindings let the researchers know that students choose ABM because of their personalinterests, and students perceived their track as a contribution to their future course because itis connected to the course that they want to take in college. Additionally, ABM strand subjectswould give them primary knowledge that would be helpful to their future course. Furthermore,ABM Students strongly agreed that the wrong choice of track might affect their future course.The ABM strand is part of the K-12 Academic Track. It focuses on financial management,business management, corporate operations, and everything that needs to be recorded. InBestlink College of the Philippines, Bulacan Inc., most Grade 11 and Grade 12 ABM studentspursued this strand because of their personal interest, and they can see that Accountancy,Business, and Management have a contribution to the course that they will take in college.The researchers recommend students know what they truly want and seek information on howtheir chosen track would impact them as they go beyond Senior High School.
Keywords: Education